2017
DOI: 10.3329/bjas.v46i2.34433
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of yearling F1 progeny of different crossbred beef cattle

Abstract: Bangladesh has a great demand of beef but it has been facing demand and supply mismatches due to insufficient production and supply of beef, low carcass yield of native cattle and recent no-cattle export policy of a long bordered neighboring country. Thus, the present work was undertaken with an objective to develop market beef cattle of average >150 Kg carcass weight by 24 months with an average FCR of <6.50 under on farm feeding and management condition. Aiming at developing breeding bulls the native dams of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…Brahman crossbred calves mean birth weight ranged from 17.52 to 27.12 kg. This result is in accordance with the findings of 24.1±1.23 kg reported by Mostari et al (2017) for Brahman × BLRI cattle breed-1, 21.40±0.24 kg reported by Haque et al (2016) for 50% Brahman crossbred calves. The observed mean birth weight in this experiment was lower than the 32.6, 35.5 and 30.7 kg average birth weight for Brahman cross calves reported by Dundon et al (2012), Cunningham et al (2005) and Antonio et al (2006).…”
Section: Breeding Bull Effect On Body Weight At Different Ages Of Bra...supporting
confidence: 93%
See 1 more Smart Citation
“…Brahman crossbred calves mean birth weight ranged from 17.52 to 27.12 kg. This result is in accordance with the findings of 24.1±1.23 kg reported by Mostari et al (2017) for Brahman × BLRI cattle breed-1, 21.40±0.24 kg reported by Haque et al (2016) for 50% Brahman crossbred calves. The observed mean birth weight in this experiment was lower than the 32.6, 35.5 and 30.7 kg average birth weight for Brahman cross calves reported by Dundon et al (2012), Cunningham et al (2005) and Antonio et al (2006).…”
Section: Breeding Bull Effect On Body Weight At Different Ages Of Bra...supporting
confidence: 93%
“…Overall calf mortality was 2.13% up to 12 months of age. This mortality rate was much lower compared to 5.26% for different beef cattle crossbred (Mostari et al, 2017), 9.7% for F1 Fogera crosses cattle in Ethiopia (Amuamuta et al, 2006), 14.5% up to 12-month of age for Local zebu × Holstein crossbred calves in Ethiopia (Ferede et al, 2014), 24.5% reported by Kebamo et al (2019) for Boran calves in Ethiopia. This improvement possibly due to increased farmers consciousness toward colostrum intake, better housing and feeding and other managemental activities during and immediately after calving.…”
Section: Calf Mortalitymentioning
confidence: 79%
“…Crossing Boran cattle with exotic breeds increases the survivability of the cross-bred cattle in hot/humid environments compared to pure exotic breeds, as found in the current study, and is consistent with the findings of other studies reported by [46][47][48][49]. This might be due to physiological and morphological modifications that crossbred animals experience in comparison to their exotic parents, which help them adapt to hot, humid environments that are typically characterized by high temperatures and humidity.…”
Section: Effect Of Genotype On Calves' Survivabilitysupporting
confidence: 92%
“…Despite, several study were reported that season did not have significant effect to WW in Bos indicus breeds cattle such as Fogera (Addisu et al, 2010), Ongole grade (Hartati et al, 2015), Brahman (Hernandez et al, 2015) and Kaswati et al (2013). BW= birth weight; WW = weaning weight; YW= yearling weight; ADG 1 = average daily gain of pre-weaning; ADG 2 = average daily gain of post-weaning crossbred cattle between Bos indicus and Bos taurus (Mostari et al, 2017). In addition, Wijono et al (2006) reported that season had significant effect to YW but did not have significant effect to WW in Ongole grade cattle.…”
Section: Effect Of Seasonmentioning
confidence: 99%